Transformative cyber security model for Malaysian government agencies - Perumal S.; Pitchay S.A.; Samy G.N.; Shanmugam B.; Magalingam P.; Albakri S.H. (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA